انهاء خدمة الموظف تحت التجربة: دراسة مقارنة - بن عمير، جاسم عبدالله محمد (جامعة البحرين - كلية الحقوق, 2015)
نص قانون الموارد البشرية في الحكومة الاتحادية الإماراتي على خضوع الموظف المعين الأول مرة لفترة تجربة مدتها ثلاثة أشهر بهدف التأكد من كفاءته وحسن سيرته التي تؤهله للقيام بمهام الوظيفة التي عين فيها. وقد عرضنا في هذا البحث: مدة فترة التجربة والمركز القانوني للموظف خلالها، وسلطة الإدارة التقديرية في إنهاء خدمة الموظف تحت التجربة سواء أثناء فترة التجربة أو بعد انتهائها ورقابه القضاء الإداري على الأسباب التي تستند إليها السلطة المختصة بإنهاء خدمة الموظف تحت التجربة لتدني مراتب الكفاءة، وأخيرا عرضنا لعملية تقييم الأداء للموظف تحت التجربة للتحقق من كفاءته أو عدمها باعتبار تقييم الأداء هو المعيار الذي حدده المشرع لقياس كفاءة الموظف في الوظيفة العامة، وأتبعنا هذا البحث بعدد من التوصيات الخاصة بضمانات إنهاء الخدمة لعدم الكفاءة بالنسبة للسلطة المختصة وللموظف الخاضع لفترة التجربة.
The Human Resources regulations in the Federal Government of the UAE stipulates that the civil servant shall be subject for a three month probation period to monitor employee efficiency and performance in tandem with the job requirement in issue. We surveyed in this study the following: The probation period and the legal status of the employee during such period. The discretionary powers of the management to terminate employee services under probation or beyond and the supervision of the judicial administration over the justifications upon which the authorized administration rest to terminate employment contract under probation period for reasons of inefficiency of performance. Finally, we surveyed the process of evaluation of employee performance to verify level of efficiency being the standard that the legislator defined to determine the performance of a civil servant. We appended this research with a number of propositions for the concerned authority and the employee concerning conditions for termination of services due to lack to of efficiency of employee under probation period.
Keywords: الموارد البشرية -- الموظفون -- الكفاءة الوظيفية -- انهاء الخدمة